Urban Socio-Economic Variables and Intra-Urban Trips in Ogun State, Nigeria - Solanke Muse Olayiwola (Indonesian Journal of Geography, 2014)
This study examines the relative influence of socio-economic variables of urban centers on intra-city tripgeneration. Data were collected on sixteen socio-economic variables and household trip generation in fourteen urbancenters of the state. The nature and degree of relationships between socio-economic variables and trips generated wereestablished through simple bivariate correlation technique. Multiple regression analysis was used to explain variablesthat predict trips generated. The principal component analysis was used to resolve observed collinearity problem in regressionanalysis.There is a strong significant positive correlation between trip generated and 13 out of sixteen socio-economicvariables. The principal component analysis on the socio-economic variables produced two components: socialand commercial component and industrial development component.The two components explain 58.68% of variationin intra-urban trips generated (F=7.830, P≤0.50), (F=13.982, P≤0.50). The industrial development component does notprovide significant explanation.The study emphasizes the need for proper planning and effective monitoring of developingof socio-economic variables in cities because of their critical influence on trip generation.